RULA method in the ergonomic analysis of an ophthalmic surgeon’s work: a case study - Ferreira, Teresa Alexandra Vaz; Carvalho, Cláudia Cristina Cabral de (O Mundo da Saúde, 2025)
Work-related musculoskeletal disorders (WRMSDs) represent a widespread occupational health issue across many countries, leading to high organizational costs and constituting one of the main causes of work disability. Ophthalmic surgery requires a high level of concentration, precision, and physical effort, often associated with the adoption of static and inadequate postures, which predispose these professionals to the development of WRMSDs. This study aimed to characterize the posture of an ophthalmic surgeon in the operating room using the RULA (Rapid Upper Limb Assessment) method. This is a descriptive case study conducted according to the Case Report (CARE) guidelines. The results revealed that the surgeon remains seated and static for extended periods, adopting potentially harmful postures. The application of the RULA method indicated an urgent need for ergonomic intervention, with recommendations including seat adjustments, arm support, and workspace reorganization. The importance of implementing regular breaks, stretching exercises, and strategies to reduce visual fatigue is also emphasized. The use of more comprehensive, complementary ergonomic assessment methods is recommended for a more complete analysis. It is concluded that ergonomic adaptation of the workstation is essential for promoting the surgeon’s health, safety, and performance, and that the RULA method is a valuable tool for identifying risks associated with WRMSDs.